Participation In Community Empowerment Through The Kampung KB Program - Sundus Pramudhita Subekti; Ilmi Usrotin Choiriyah (Universitas Muhammadiyah Sidoarjo, 2022)
This study aims to describe and analyze community empowerment through the Kampung KB program in Ketegan Village, Tanggulangin District and to determine the supporting and inhibiting factors for community empowerment in the KB Village. The research method carried out by the researcher is a qualitative descriptive method. The technique of determining the informants in this study used a purposive sampling technique. Data collection techniques in this study were obtained through interviews, observation, and documentation. fish-based food processor by PLKB Tanggulangin Regency. Based on the results of the study, it is shown that the main target of this program is the community, especially in Ketegan Village. From the community side, they gave a positive response in the implementation of the family planning program in the form of community participation in providing information.